Effect of potassium levels on teff (Eragrostis tef (Zucc.) Trotter) growth and yield in Central Highland Vertisols of Ethiopia - Mulugeta Demiss; Tekalign Mamo; Sheleme Beyene; Selamyihun Kidanu (Eurasian Journal of Soil Science, 2020)
Nutrient depletion and imbalance are among the major attributes that contribute to declining soil productivity in the highlands of Ethiopia. The blanket fertilizer recommendation, which considered only urea and Di-ammonium phosphate (DAP), was used over the past four decades to improve soil fertility for enhancing crop production. Nevertheless, the average national yields of small cereal including teff were low, despite application of nitrogen and phosphorus (NP) fertilizers. On-farm trials were conducted in the 2015/16 and 2016/17 cropping seasons at 18 locations on Ethiopian highland Vertisols to determine the response of teff to potassium (K) fertilization along with other limiting nutrients. Five K levels (0, 30, 60, 90 and 120 kg ha-1) in the form of murate of potash (KCl) were used in randomized complete block design with three replications. Separate analysis of variance was conducted for each sites and year. Least Significant Difference (LSD) test at P ≤ 0.05 was used to separate means whenever there were significant differences. Analysis of variance revealed a highly significant difference (P < 0.01) between treatments in both straw and grain yields and tissue nitrogen (N) and K concentrations of teff over the two-cropping seasons in 67% of the test locations. Additionally, responses to K were obtained on soils with available K test ranging between 166 and 282 mg kg-1. The Ca: K and Mg: K ratios were strongly and negatively correlated with relative yield and the correlations suggest that soil with Ca: K > 50:1 and Mg: K >15:1 are likely to respond to potassium fertilization. The yield advantage accrued due to K application ranged from 30 to 77% in 2015/16 and 8 to 51% in 2016/17 seasons. The economic optimum K fertilizer application rates varied between 60 kg K ha-1 in 44% of the sites to 90 kg K ha-1 in 23% of the sites. The findings highlighted the need for revisiting fertilizer program to enhance the yield and nutrient uptake of teff in K responsive soils and developing critical levels for K in the study sites.